2015
DOI: 10.1155/2015/876825
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effects of Salidroside from Exhaustive Exercise-Induced Heart Injury by Enhancing thePGC-1αNRF1/NRF2Pathway and Mitochondrial Respiratory Function in Rats

Abstract: Objective. To test the hypothesis that salidroside (SAL) can protect heart from exhaustive exercise-induced injury by enhancing mitochondrial respiratory function and mitochondrial biogenesis key signaling pathway PGC-1α–NRF1/NRF2 in rats. Methods. Male Sprague-Dawley rats were divided into 4 groups: sedentary (C), exhaustive exercise (EE), low-dose SAL (LS), and high-dose SAL (HS). After one-time exhaustive swimming exercise, we measured the changes in cardiomyocyte ultrastructure and cardiac marker enzymes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 18 publications
3
26
2
Order By: Relevance
“…Nrf2 is moreover a downstream transcription factor for PGC-1α (peroxisome proliferatoractivated receptor gamma coactivator-1 alpha) gene. The Nrf2 and PGC-1α proteins interact with each other as well (the latter as co-factor) activating mitochondria-related genes, mentioned earlier in this chapter [142][143].…”
Section: The Pgc-1α-nrf2 Axis 21mentioning
confidence: 78%
“…Nrf2 is moreover a downstream transcription factor for PGC-1α (peroxisome proliferatoractivated receptor gamma coactivator-1 alpha) gene. The Nrf2 and PGC-1α proteins interact with each other as well (the latter as co-factor) activating mitochondria-related genes, mentioned earlier in this chapter [142][143].…”
Section: The Pgc-1α-nrf2 Axis 21mentioning
confidence: 78%
“…RS is a member of the Rhodiola family that is grown in Tibet in China [ 27 ]; this natural plant pharmaceutical is well known for its physiological benefits such as elimination of fatigue [ 43 ], enhancement of EC [ 28 ], and prolongation of lifespan [ 29 , 30 ]. Several recent studies have demonstrated that RS activates autophagy [ 44 ] and mitochondrial biogenesis in endothelial cells [ 33 ] and the myocardium in rats [ 45 ]. Here, we report for the first time that RS enhances the function of mitochondria in SCM and activates autophagy and mitochondrial biogenesis in mouse skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the CREB pathway results in the phosphorylation of CREB (p-CREB), and p-CREB binds the CREB-response element (CRE), located proximal to the PGC-1α promoter, and activates PGC-1α transcription 42 , 43 . Additionally, GSK-3β plays a role in regulating PGC-1α protein stability, negatively regulating PGC-1α by promoting its proteasomal degradation 44 , 45 .…”
Section: Discussionmentioning
confidence: 99%